The determination of sodium salicylate effect to body weights and fatty acid values in the frontal lobe of brain on the immobilized rats - Dayangac, A.; Citil, S.; Bahsi, M.; Aktas, T.; Yilmaz, O. (Wiley-Blackwell, 2014)
[Abstract Not Available]